Transient and stationary characteristics of a packet buffer modelled as an MAP/SM/1/b system - Rusek, Krzysztof; Janowski, Lucjan; Papir, Zdzisław (Zielona Góra: Uniwersytet Zielonogórski)
A packet buffer limited to a fixed number of packets (regardless of their lengths) is considered. The buffer is described as a finite FIFO queuing system fed by a Markovian Arrival Process (MAP) with service times forming a Semi-Markov (SM) process (MAP/SM/1/b in Kendall`s notation). Such assumptions allow us to obtain new analytical results for the queuing characteristics of the buffer.
Keywords: router interface; Markovian arrival process; semi-Markov service time; hidden Markov model; finite-buffer queue; packet losses; first passage time